Dynamic macroeconomic implications of immigration - Conny Olovsson; Karl Walentin; Andreas Westermark (Sveriges Riksbank, 2021)
International immigration flows are large, volatile and have recently increased. This paper is the first to study the dynamic effects of immigration shocks on the economy within a search and matching framework. Since the microdata indicates that some of the key macroeconomic effects of immigration are largest in the short run, a steady state analysis would be insufficient. To construct a quantitatively relevant general equilibrium framework, we use extensive Swedish microdata. We then study the effect of a large immigration shock on various macroeconomic aggregates. Due to compositional effects, there is a substantial negative effect on GDP per capita and the employment rate on impact that then decreases over time.
Keywords: J21; J31; J61; 330; Immigration; dynamics; search and matching